Ethical branding in a divided world: how political orientation motivates reactions to marketplace transgressions - Allard, Thomas (2022)
In today's marketplace, users (e.g., purchasers, influencers) are increasingly the “face” of brands to potential consumers, increasing the risk for brands should these users act poorly. Across seven studies, we document that political orientation moderates the desire for punishment toward users of ethical (vs. conventional) brands who commit moral transgressions. In response to identical marketplace transgressions, we observe that liberals punish ethical brand users less than conventional brand users. In contrast, conservatives punish the same users of ethical brands more than conventional brand users. We document that this bias stems from how people interpret the inconsistency between the ethical branding and the act of transgression, rather than from a group-identity effect, showing how it does not arise in the absence of inconsistent information or when consumers are not able to integrate the inconsistent information to their judgments. We also investigate an avenue by which firms can reframe their ethical branding to reduce this politically motivated bias. We discuss this work's implications for moral judgments, marketplace attribute formation, and the branding of ethical goods in a politically divided world.